A Ferroelectric/Electrochemical Modulated Organic Synapse for Ultraflexible, Artificial Visual‐Perception System. Issue 46 (25th September 2018) - Wang, Hanlin; Zhao, Qiang; Ni, Zhenjie; Li, Qingyuan; Liu, Hongtao; Yang, Yunchang; Wang, Lifeng; Ran, Yang; Guo, Yunlong; Hu, Wenping; Liu, Yunqi
Abstract: Human eyes undertake the majority of information assimilation for learning and memory. Transduction of the color and intensity of the incident light into neural signals is the main process for visual perception. Besides light‐sensitive elements that function as rods and cones, artificial retinal systems require neuromorphic devices to transform light stimuli into post‐synaptic signals. In terms of plasticity timescale, synapses with short‐term plasticity (STP) and long‐term potentiation (LTP) represent the neural foundation for experience acquisition and memory formation. Currently, electrochemical transistors are being researched as STP–LTP devices. However, their LTP timescale is confined to a second‐to‐minute level to give unreliable non‐volatile memory. This issue limits multiple‐plasticity synapses with tunable temporal characteristics and efficient sensory‐memory systems. Herein, a ferroelectric/electrochemical modulated organic synapse is proposed, attaining three prototypes of plasticity: STP/LTP by electrochemical doping/de‐doping and ferroelectric‐LTP from dipole switching. The device supplements conventional electrochemical transistors with 10000‐second‐persistent non‐volatile plasticity and unique threshold switching properties. As a proof‐of‐concept for an artificial visual‐perception system, an ultraflexible, light‐triggered organic neuromorphic device (LOND) is constructed by this synapse. The LOND transduces incident light signals with different frequency, intensity, and wavelength into synaptic signals, both volatile and non‐volatile. Abstract : Inspired by the human retina, a light‐triggered, organic neuromorphic device (LOND) is presented. The LOND is a ferroelectric/electrochemical synapse gated by broad‐band photodetectors. The synapse produces short‐ and long‐term memory by electrochemical doping and ferroelectric switching. With this synapse for signal readout, the LOND transduces green light into non‐volatile memory and NIR into volatile signals, achieving a color‐perception functionality.